Coping with the postponement boundary problem: an empirical investigation in global food supply chains - Prataviera, Lorenzo Bruno; Moretti, Emilio; Tappia, Elena (Emerald, 2022)
Purpose – The postponement boundary problem entails that duties and cross-border trade complexity can lead companies to geographically postpone operations to downstream global facilities. The present study aims at investigating the problem to provide insights into the drivers behind the choice of different postponement strategies for global food supply chains. Design/methodology/approach – A single case study was conducted considering an Italian company exporting olive oil toward the United States. Two global postponement strategies, previously formalized in the literature, were tailored for food supply chains. A multi-methodological approach was adopted, combining data obtained through exploratory case research with empirically-grounded analytical modeling. A sensitivity analysis was also performed, to investigate outcomes related to the considered problem when changing key parameters. Findings – Bulky and heavy packing materials account for a big percentage of finished products’ volume and weight, and this can deeply affect strategies’ cost-effectiveness. Postponing packaging operations could allow for taking advantage of lower tariffs levied on bulk goods, contributing to significantly lower duties to be paid. However, important trade-offs could arise related to the required investments, and the fiscal regulatory frameworks must be carefully examined. Originality/value – This study offers an empirical investigation of the postponement boundary problem, which is largely unexplored in the current literature. It also tackles an understudied empirical context as global food supply chains. It summarizes the drivers behind and explores the costs related to the implementation of different strategies, offering an original quantitative approach that could support practitioners’ decision-making. Lastly, it formalizes five propositions that could pave the way for further research inquiries.
Keywords: Postponement boundary problem; Food supply chains; Duties; Case study; Analytical model